ANTIBACTERIAL TEST OF ENHALUS ACOROIDES SEAGRASS AGAINST BACTERIA SALMONELLA TYPHI - Amin, Abd Aziz; Amrillah, Attabik M (Directorate of Research and Community Service (DRPM), 2023)
The use of antibacterial from natural ingredients can as an alternative, one of them is seagrass Enhalus acoroides which is known to have inhibiting active compounds bacterial growth. Metabolites from seagrass are known to be biologically active is an important biomedical and can be used as a drug potential. The use of antibacterial from natural ingredients is alternative approach. Bacteria Salmonella typhi is a genus of gram-negative enterobacteria sticks that cause typhoid, paratyphoid, and foodborne diseases and resistant bacteria. Therefore, the purpose of this research was to analyze the activity test antibacterial on Enhalus acoroides seagrass against Salmonella typhi bacteria. The methods used in this study were seagrass extraction, phytochemical tests, and antibacterial activity tests. The results obtained from the research are crude extracts with solvents methanol, ethyl acetate and n-hexane with a concentration of 500 ppm was the most effective extract concentration in inhibiting bacterial growth Salmonella typhi with a weak category. Furthermore, characteristic Antibacterial crude extract of seagrass Enhalus acoroides was bacteriostatic. This study suggests that the influence of polarity types solvent on antibacterial activity of seagrass extract Enhalus acoroides against the growth of Salmonella typhi bacteria.